Strength and Deformation Analysis on Car Door Design for Energy Saving Contest - Pradanawati, Sylvia Ayu; Harnany, Dinny; Riyandwita, Byan Wahyu; Ikhtiar, Apri Roni; Sasongko, Dimas Wahyu; Khoiruddin, Ahmad Imam; Nazera, Afif Sulthan Rasyid; Rusydi, Muhammad; Saputra, Yafendra Arie; Widodo, Rizky Susilo (Journal of Emerging Supply Chain, Clean Energy, and Process Engineering, 2024)
The car door is a vital component of an automobile, playing a key role in passenger safety during accidents. For an energy-saving competition, the strength of a car prototype's door was thoroughly examined using Finite Element Analysis (FEA). This study involved three testing methods: pole side impact, side impact, and door slam tests. Simulations were conducted using the Finite Element Method (FEM) with aluminum alloy 6061-T4, type-E fiberglass, and type-S fiberglass as materials. These materials were selected based on their stress properties, mass, and cost. The simulation indicated that the side impact test produced the highest stress levels, especially in the fiberglass materials. While the aluminum alloy exhibited higher von Mises stress than its tensile strength in one case, both types of fiberglass maintained safety as their tensile strengths exceeded the maximum von Mises stress. The pole side impact test showed aluminum's highest stress and deformation, whereas fiberglass materials showed higher stress and deformation in the side impact test. The door slam test demonstrated minimal stress and deformation across all materials. Among the three, type-E fiberglass demonstrated the most favorable and safest performance. Consequently, type-E fiberglass is highly recommended as the ideal material for the car prototype's door.